Subiekt semantyczny w rosyjskich zdaniach typu никому нельзя верить w porównaniu z językiem polskim - Rudyk, Anna (Przegląd Rusycystyczny, 2009)
СЕМАНТИЧЕСКИЙ СУБЪЕКТ В РУССКИХ ПРЕДЛОЖЕНИЯХ ТИПА НИКОМУ НЕЛЬЗЯ ВЕРИТЬ ПО СРАВНЕНИЮ С ПОЛЬСКИМ ЯЗЫКОМ Резюме Статья посвящена семантическому субъекту в русских предложениях типа Никому нельзя верить и в их польских эквивалентах. В анализируемых конструкциях субъект может быть назван формой дательного падежа, может восстанавливаться из контекста предложения или быть устраненным. В польском переводе для выражения сематичес-кого субъекта может также послужить личное окончание глагола. SEMANTIC SUBJECT IN THE RUSSIAN SENTENCES OF THE TYPE НИКОМУ НЕЛЬЗЯ ВЕРИТЬ COMPARED WITH POLISH ONES Summary The article deals with the way of expressing a semantic subject in Russian sentences of the type Никому нельзя верить and their Polish equivalents. The semantic subject can be con-veyed explicitly in the form of the dative case. It can also appear from the context or remain unnamed due to meaning generalization or the absence of information concerning its referent. The personal fl exion of the verb can express the subject in Polish translations well.